1963
DOI: 10.1172/jci104805
|View full text |Cite
|
Sign up to set email alerts
|

Regional Pulmonary Function Studied With Xenon133 in Patients With Bronchial Asthma*

Abstract: It has been known for some years that there may be impairment in the distribution of an inert gas in the lungs of patients with bronchial asthma at a time when the disease appears to be in remission (1, 2). Maximal ventilatory air flow may also be reduced in the absence of symptoms (2).A recently described technique for the study of regional distribution of pulmonary ventilation and perfusion using xenon'33 (3) appeared to be suitable for the study of zonal variations in function in these patients. METHODSSele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

1964
1964
1986
1986

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…This underperfusion was not entirely effective from a gas exchange point of view since VA/Q was relatively low in hypoventilated regions; if there had been no change in perfusion distribution, however, over-all gas exchange obviously would have been more inefficient. The normal blood flow distribution found in patients with asthma in a previous study (2) probably was due to their upright posture; since blood flow distribution in the erect normal subject is uneven (9), abnormalities are difficult to detect. Since it is likely that the lung parenchyma was morphologically normal in these patients, regional decreases in flow probably were functional in origin.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…This underperfusion was not entirely effective from a gas exchange point of view since VA/Q was relatively low in hypoventilated regions; if there had been no change in perfusion distribution, however, over-all gas exchange obviously would have been more inefficient. The normal blood flow distribution found in patients with asthma in a previous study (2) probably was due to their upright posture; since blood flow distribution in the erect normal subject is uneven (9), abnormalities are difficult to detect. Since it is likely that the lung parenchyma was morphologically normal in these patients, regional decreases in flow probably were functional in origin.…”
Section: Resultsmentioning
confidence: 84%
“…Studies with 133xenon (133Xe) in this laboratory (2) showed hypoventilation of lung regions in symptom-free patients with asthma, and it was concluded that these regions probably had low ventilation/perfusion ratios (VA/Q). This conclusion was supported by the findings of Ledbetter, Bruck, and Farhi (3), who measured nitrogen tension in both alveolar gas and arterial blood in patients with asthma and found lung units with abnormally low alveolar VA/Q.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…If it is assumed that the same equilibrium existed under control conditions, Cao a(PB -47) FAo 760 [6] and It is also possible to obtain the relative ventilation-perfusion ratio of the slow compartment (i.e., the value of that ratio for this compartment in respect to that of the whole lung, as expressed in Equation 7) by dividing FA/FAo by Ca/Cao measured at the same time during the washout.…”
Section: Theorymentioning
confidence: 99%
“…Some are based on injection or inhalation of radioactive materials (3)(4)(5)(6), but are too complicated or too costly for general use. Finley (7) has reported a method of estimating perfusion of poorly ventilated alveoli that requires simultaneous recording of alveolar CO2 and N2 (from which alveolar 02 is calculated) and arterial 02 tension.…”
mentioning
confidence: 99%